PENGARUH STRUKTUR MODAL, PROFITABILITAS, PERTUMBUHAN PERUSAHAAN TERHADAP HARGA SAHAM: STUDI KASUS PT. UNILEVER TBK. PERIODE 2018 - 2022 - Ari Sulistyowati; Anggraini Putri Otorus Carolina, Muhammad Rizal, Naura Salsabilla, Sofie Aura Rahma (Adisam Publisher, 2024)
This research aims to analyze the influence of capital structure, profitability and company growth on the share price of PT. Unilever Tbk. during the 2018-2022 period. The research method used is regression analysis using financial data and PT share prices. Unilever Tbk. obtained from financial reports and the stock market during the research period. The results of this study indicate that the company's capital structure, measured by the debt to equity ratio, has a significant influence on share prices. Profitability, represented by the ratio of net profit to sales, also has a significant influence on stock prices. Meanwhile, company growth, measured by sales or asset growth, does not show a significant influence on share prices. These findings can provide insight to corporate decision makers, investors and regulators regarding the factors that can influence PT share prices. Unilever Tbk. By understanding the relationship between capital structure, profitability, growth and stock price, stakeholders can make better decisions in managing their investments in the stock market.